STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM MENGEMBANGKAN BUDAYA RELIGIUS DI MTs NEGERI 1 PURWOREJO - Siti Maysaroh; Muhlil Musolin; Fitrohtul Khasanah (STKIP Pesisir Selatan, 2026)
The decline in internalization of religious values among students as a result of digital culture. Madrasahs require strong leadership strategies to overcome the impact of digital culture, especially to foster a strong religious environment. The purpose of this study was to determine the leadership strategies of madrasah principals in developing a religious culture and the inhibiting and supporting factors at MTs Negeri 1 Purworejo. This study used a qualitative methodology with a phenomenological approach. The research subjects included madrasah principals, religious teachers, and students. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results showed that the madrasah principal's strategy plays a role as an educator, manager, administrator, supervisor, leader, innovator, and motivator in building a religious culture in madrasahs. The strategies implemented include organizing religious activities, continuous supervision and monitoring, appreciation for teachers and students, and coaching for students. Supporting factors for the success of religious culture include support from all madrasah members and adequate worship facilities, while inhibiting factors are the influence of digital culture and limited time for religious activities.